Sarcopenic Dysphagia in the elderly: an integrativa review (Research, Society and Development, 2022)
Objective: Identifying the sarcopenic characteristics related to swallowing of old people. Methodology: A quantitative research conducted from September/2020 to October/2020, initially searched for articles published in the last 10 years, previously defined in the context of the theme: "Dysphagia" and "Sarcopenia" and "Aging" associated with/or not the "swallowing disorder" in the databases and virtual library/bibliographic repository. An analytical reading of the abstracts, method and conclusion of the articles organized in an Office 2019 Excel spreadsheet was performed to discuss the results, which was based on the interpretation and synthesis of these. Results: Sarcopenic dysphagia is related both to the reduction of tongue and skeletal muscle mass and to the increase in tongue muscle intensity, jaw opening force, malnutrition as an outcome for oral sarcopenia leading to dysphagia with aspiration, lower laryngeal elevation and wider pharyngeal area. Among men, the decreased physical strength is associated with a reduction in oral and pharyngeal function; on the other hand, in women this fact did not occur with the same frequency. Conclusion: Prevention of whole-body sarcopenia is the best choice (option) for prevention for sarcopenic dysphagia.